Quality of life in patients with pemphigus - Wysoczyńska, Katarzyna; Żebrowska, Agnieszka; Waszczykowska, Elżbieta (Dermatology Review/Przegląd Dermatologiczny, 2013)
Introduction . Pemphigus is a group of chronic autoimmune diseases clinically characterized by bullae and erosions on the skin and/or mucous membranes. These symptoms are often accompanied by pain, itching and skin burning. Physical symptoms, chronic nature of the disease and the treatment have a great influence on physical and mental condition of patients. Objective . To assess the impact of pemphigus on quality of life in patients with pemphigus. Material and methods . The study comprised 22 patients with pemphigus and 22 volunteers without skin diseases. The quality of life was measured using the SF-36 general health related quality of life questionnaire and two skin-specific scales, SKINDEX-29 and DLQI. Results . Patients with pemphigus showed a markedly impaired overall quality of life (QoL) compared with control subjects (total SF-36 54.13 vs. 72.00, p = 0.01). The mean scores obtained by the patients were in the DLQI scale 4 ±5.87 and SKINDEX-29 56 ±23.44. The factors influencing decreased QoL are presence of subjective skin lesions and symptoms. Conclusions . Our data indicate that pemphigus has an important role in patients’ quality of life. Evaluation of quality of life in these patients can be a very useful component of medical consultation.